Biomolecular proteomics discloses ATP synthase as the main target of the natural glycoside deglucoruscin. Issue 10 (1st August 2016) - del Gaudio, Federica; Festa, Carmen; Mozzicafreddo, Matteo; Vasaturo, Michele; Casapullo, Agostino; De Marino, Simona; Riccio, Raffaele; Monti, Maria Chiara
Abstract : Extracts of Ruscus aculeatus are rich of deglucoruscin, a spirostanol glycoside, which is able to interact with ATP synthase and modulate its activity. Abstract : Extracts of Ruscus aculeatus are a rich source of bioactive steroidal glycosides, such as ruscogenins which are reported to act against chronic venous disorders. Nowadays, several preparations of its roots, commonly used in traditional medicine, are on the market as food supplements for health care and maintenance. Although spirostanol deglucoruscin is one of the main metabolites in these extracts, literature reports about its pharmacological profile are scarce. In this paper, a multi-disciplinary approach, based on chemical proteomics, molecular modelling and bio-organic assays, has been used to disclose the whole interactome of deglucoruscin and the F0–F1 ATP synthase complex has been found as its main target.